Advances and challenges in the production of extracellular thermoduric pullulanases by wild-type and recombinant microorganisms: a review. (3rd April 2019) - Akassou, Mounia; Groleau, Denis
Abstract: Thermoduric pullulanases, acting as starch-debranching enzymes, are required in many industrial applications, mainly in the production of concentrated glucose, maltose, and fructose syrups. To date, however, a single pullulanase, from Bacillus acidopullulyticus, is available on the market for industrial purposes. This review is an investigation of the major advances as well as the major challenges being faced with regard to optimization of the production of extracellular thermoduric pullulanases either by their original hosts or by recombinant organisms. The critical aspects linked to industrial pullulanase production, which should always be considered, are emphasized, including those parameters influencing solubility, thermostability, and catalytic efficiency of the enzyme. This review provides new insights for improving the production of extracellular thermoduric pullulanases in the hope that such information may facilitate their commercial utilization and potentially be applied to the development of other industrially relevant enzymes.